INTEGRSI KECERDASAN (AI) DALAM DESAIN KURIKULUM ABAD KE-21 : STUDI KASUS PEMBELAJARAN ADAPTIF DI MADRASAH - Adinata, Dwiraja; Hadi Holib, Habibie; Novalia, Jelita; Triani, Nofi; Abdurrahmansyah, Abdurrahmansyah (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to explore the integration of artificial intelligence (AI) in the design of adaptive learning curricula in 21st-century madrasahs. The method employed is a literature review analyzing various sources on AI application in Islamic education. The results reveal that AI enhances personalized learning, strengthens 21st-century skills such as critical and creative thinking, and supports Islamic character development. Implementation challenges include limited infrastructure, teacher competency, and education regulations. Optimization strategies involve teacher training, infrastructure development, supportive policies, and innovative AI-based learning media to effectively adapt madrasahs to the dynamic digital era.